Implementasi Prinsip Yurisdiksi Universal Mengenai Pemberantasan Kejahatan Perompakan Laut Di Indonesia - Dian Korea (UIR Law Review, 2018)
The high seas are all parts of the sea that are not included in the exclusive economic zone, territorial sea, inland waters of a country, or in the archipelagic waters of an archipelago country. Consequently, the case of the interpretation of the case. This happens with the MV Ship. Sinar Kudus is an Indonesian ship that is a jurisdiction of the Indonesian state. For the case, Indonesia is obliged to participate in resolving the piracy case that happened on the MV ship. Sinar Kudus, so the jurisdiction of the Indonesian state against the MV ship. The Holy Light captured by Somali pirates is a passive nationality jurisdiction. In this jurisdictional principle, Indonesia has the right to protect its citizens who are victims of crimes abroad. Constraints in the implementation of Indonesian state jurisdiction over MV Ship. Sinar Kudus which was held hostage by Somali pirates such as MV ship. The holy rays while sailing in international waters were not accompanied by Indonesian warships, so the Indonesian Navy could not directly attack the pirates at the time of piracy. MV Ship. The holy rays are brought to the territorial waters of Somalia by pirates, so what prevails here is the jurisdiction of the Somali state. Seeing the weakness of law enforcement in Somalia makes it difficult for Indonesia to cooperate in the release of the crew of the Sinar Kudus ship held hostage by Somali pirates. Indonesia voted for negotiations on the release of the crew of Sinar Sudus for the safety of crew members being held hostage by Somali pirates.